2021
DOI: 10.3389/fcell.2021.596702
|View full text |Cite
|
Sign up to set email alerts
|

Elastin Structure, Synthesis, Regulatory Mechanism and Relationship With Cardiovascular Diseases

Abstract: As the primary component of elastic fibers, elastin plays an important role in maintaining the elasticity and tensile ability of cardiovascular, pulmonary and many other tissues and organs. Studies have shown that elastin expression is regulated by a variety of molecules that have positive and negative regulatory effects. However, the specific mechanism is unclear. Moreover, elastin is reportedly involved in the development and progression of many cardiovascular diseases through changes in its expression and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 74 publications
0
22
0
Order By: Relevance
“…Previous studies reported that fibril forming collagen was highly correlated with a variety of diseases, including skin blistering disease bullous pemphigoid, osteogenesis imperfecta, and Ehlers-Danlos syndrome ( Ricard-Blum, 2011 ). Elastic fiber has been associated with cardiovascular diseases, such as myocardial ischemia-reperfusion and atherosclerosis ( Wang et al., 2021 ). In terms of disease related to both collagenous and elastic fiber, it has been found that collagenous and elastic fiber levels were substantially elevated during interstitial pneumonia, contributing to vascular ECM remodeling and scar formation ( Parra et al., 2007 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported that fibril forming collagen was highly correlated with a variety of diseases, including skin blistering disease bullous pemphigoid, osteogenesis imperfecta, and Ehlers-Danlos syndrome ( Ricard-Blum, 2011 ). Elastic fiber has been associated with cardiovascular diseases, such as myocardial ischemia-reperfusion and atherosclerosis ( Wang et al., 2021 ). In terms of disease related to both collagenous and elastic fiber, it has been found that collagenous and elastic fiber levels were substantially elevated during interstitial pneumonia, contributing to vascular ECM remodeling and scar formation ( Parra et al., 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fibril forming collagen subfamily contains collagen I, II, III, V, XI, XXIV, XXVII and collagen I is the most prevalent collagen in the body ( Ricard-Blum, 2011 ). Elastin was the core component of elastic fibers ( Wang et al., 2021 ). The expression of associated genes was also investigated at the mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elastin is the main protein responsible for the elastomeric and tensile properties of ECM and many relevant tissues, such as the pulmonary and cardiovascular ones [49] . As such, elastin is a promising macromer for angiogenesis and cardiovascular tissue regeneration [50] .…”
Section: Macromers Chemistrymentioning
confidence: 99%
“…Collagen is of particular interest as it is known to be heavily involved in ECM remodeling related to both aging and disease. Unlike elastin, which cannot be produced by the body after developmental years, collagen repair and regeneration in the aortic ECM occurs throughout a person's life (Wang et al, 2021), and these processes may occur at an accelerated rate to compensate for elastin fragmentation and reduction. As collagen is intimately related to the structural integrity and biomechanical performance of the aorta, there have been several studies on its role in relation to AsAA development and progression.…”
Section: Introductionmentioning
confidence: 99%